2004
DOI: 10.1103/physreve.69.021107
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic resonance between dissipative structures in a bistable noise-sustained dynamics

Abstract: We study an extended system that without noise shows a monostable dynamics, but when submitted to an adequate multiplicative noise, an effective bistable dynamics arises. The stochastic resonance between the attractors of the noise-sustained dynamics is investigated theoretically in terms of a two-state approximation. The knowledge of the exact nonequilibrium potential allows us to obtain the output signal-to-noise ratio. Its maximum is predicted in the symmetric case for which both attractors have the same no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…In our previous work [15] we have found that the dependence of the SNR as a function of λ is maximum at the symmetric situation λ = λ c = 0.8, where both stable structures (φ 0 and φ s ) have the same stability (…”
Section: B System Size Stochastic Resonancementioning
confidence: 99%
See 4 more Smart Citations
“…In our previous work [15] we have found that the dependence of the SNR as a function of λ is maximum at the symmetric situation λ = λ c = 0.8, where both stable structures (φ 0 and φ s ) have the same stability (…”
Section: B System Size Stochastic Resonancementioning
confidence: 99%
“…The basic model to be considered in this section is the same one studied in [15], and consist of the following ensemble of nonlinear coupled oscillators, described in terms of a continuous field…”
Section: Multiplicative Noise Case a Brief Review Of The Modelmentioning
confidence: 99%
See 3 more Smart Citations